Infiltration in Relation to Slope Characteristics, Antecedent Soil Moisture and Other Soil Properties - Sharma, K D; Singh, H P; Pareek, O P; Yadav, R C (Annals of Arid Zone, 2016)
Correlation and regression analyses using data On infiltration rate, degree and length of slope, antecedent soil moisture indices, soil texture and sorptivity from 16 runoff plots having different slopes and slope lengths were carried out. Water infiltration into the soil took place through the water free pores being directly proportional to pore volume (r = 0.5468) at field capacity. As such, it was found to be inversely proportional to antecedent moisture (r = - 0.5468) and relative moisture content (r=-0.4952). A negative correlation was obtained between infiltration rate and silt content (r = -0.6583) as a result of closing of pore space by silt particles which disperse easily under low clay content. Major infiltration in unsaturated sandy soil was assigned to capillarity (r=0.8157). It was not found to be correlated with slope, length of run, sand and clay contents. The multiple correlation coefficients between infiltration rate and other soil properties were higher and significant. 48.03% variation in the infiltration rate was accountable to the soil texture alone whereas 93.97% variation was attributed to antecedent soil moisture content and the soil texture.